2019
DOI: 10.1136/annrheumdis-2018-214367
|View full text |Cite
|
Sign up to set email alerts
|

Risk of serious infections in tocilizumab versus other biologic drugs in patients with rheumatoid arthritis: a multidatabase cohort study

Abstract: ObjectiveTo investigate the rate of serious bacterial, viral or opportunistic infection in patients with rheumatoid arthritis (RA) starting tocilizumab (TCZ) versus tumour necrosis factor inhibitors (TNFi) or abatacept.MethodsUsing claims data from US Medicare from 2010 to 2015, and IMS and MarketScan from 2011 to 2015, we identified adults with RA who initiated TCZ or TNFi (primary comparator)/abatacept (secondary comparator) with prior use of ≥1 different biologic drug or tofacitinib. The primary outcome was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
118
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 38 publications
5
118
1
7
Order By: Relevance
“…15,16 In general tocilizumab is well tolerated but can induce neutropenia, and an increased risk of developing infections has been reported. 17,18 Furthermore, it may predispose to a delay in detecting active infection because of the masking effect of a suppressed C reactive protein (CRP) response. Interestingly, however, only one of 12 patients in our cohort developed neutropenia during their ICU stay.…”
Section: Resultsmentioning
confidence: 99%
“…15,16 In general tocilizumab is well tolerated but can induce neutropenia, and an increased risk of developing infections has been reported. 17,18 Furthermore, it may predispose to a delay in detecting active infection because of the masking effect of a suppressed C reactive protein (CRP) response. Interestingly, however, only one of 12 patients in our cohort developed neutropenia during their ICU stay.…”
Section: Resultsmentioning
confidence: 99%
“…16,17 In general tocilizumab is well tolerated but can induce neutropenia, and an increased risk of developing infections has been reported. 18,19 Furthermore, it may predispose to a delay in detecting active infection because of the masking effect of a suppressed C reactive protein (CRP) response. Interestingly, however, only one of 12 patients in our cohort developed neutropenia during their ICU stay.…”
Section: Resultsmentioning
confidence: 99%
“…According to a previous study, the main concern regarding tocilizumab administration is the occurrence of severe bacterial infection. 51 However, only very few studies have reported data on severe infection in patients underwent tocilizumab, and it was de nitely not a contraindication for tocilizumab administration, particularly in critical patients.…”
Section: Discussionmentioning
confidence: 99%